Community determinants of mental health in women victims of armed conflict: A study in Montes de María, Colombia: Determinantes comunitarios de la salud mental en mujeres víctimas del conflicto armado: un estudio en los Montes de María, Colombia - Rocha Márquez, Sonia Elena; Rodríguez Rocha, Abelardo; Carruyo Duran, Norcelly; Kunzell Jiménez, José Alberto; Quintero Quintero, Wilson Emilio (Gaceta Médica de Caracas, 2026)
Introduction: Mental health emerges as an essential element of overall well-being; its importance is amplified in contexts characterized by armed conflict, where suffering and violence significantly impact daily life. Objective: To understand the community determinants of mental health in women victims of armed conflict in the Montes de María region of Colombia. Methodology: The study employed a qualitative, interpretive approach grounded in ethnography. Purposive sampling was used. The techniques employed included in-depth interviews, social mapping, and participant observation. Data analysis was performed using thematic coding. Information was triangulated to ensure rigor and interpretive validity. The research focused on the municipalities of El Carmen de Bolívar (Bolívar), San Onofre (Sucre), and María la Baja (Bolívar), located in the Montes de María subregion of Colombia, an area historically impacted by armed conflict and characterized by limited access to mental health services. The participants were eighteen adult women, direct victims of Colombian armed violence, who had experience in community organizing processes in the selected municipalities.